Advanced graphics with the ibm personal computer - Angell, Ian O. ([S.l.] : Wiley, 1985)
Presents a comprehensive introduction to computer graphics using BASIC on the IBM PC. Provides in-depth coverage of pixel block and character graphics, video games or low-resolution graphics, the construction of data graphs, two- and three-dimensional graphics, the set-up of complex objects, hidden line and surface algorithms, and perspective and stereoscopic views. Background mathematics such as coordinate geometry and matrix manipulation are explained in detail, and program segments and extensive illustrations are provided.